The Role Of Medical Innovation In Supporting The Sustainability Of The Professional Performance Of Paramedics In The Saudi Red Crescent Authority (The Review of Diabetic Studies, 2025)
The purpose of the study was to expose the contribution of medical innovation towards attaining sustainable professional practice amongst Saudi Red Crescent Authority (SRCA) technicians. This was achieved through the determination of their awareness on the current medical technologies and how these technologies affect the quality of services delivered and their field efficiency. The research design was descriptive-analytical, which involved the use of questionnaire with 15 questions that were spread on five broad axes as: awareness of innovation, the influence of innovation on performance, training and technical competence, institutional support, and general challenges. Two hundred field paramedics were given questionnaire. It yielded significant results in that the degree of adoption of medical innovation was correlated with better professional performance, higher degrees of satisfaction and professional motivation. The paper has emphasized the value of the unceasing investment in training and providing a challenging institutional environment as the key to innovation and attainment of sustainable professional performance.